2016
DOI: 10.1016/j.atherosclerosis.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Possible roles of platelet-derived microparticles in atherosclerosis

Abstract: Platelets and platelet-derived microparticles (PMPs) play important roles in cardiovascular diseases, especially atherosclerosis. Continued research has revealed that PMPs have numerous functions in atherosclerosis, not only in thrombosis formation, but also by induction of inflammation. PMPs also induce formation of foam cells. Recent evidence strongly indicates a significant role of PMPs in atherosclerosis. Here, current research on the function of PMPs in atherosclerosis is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 76 publications
1
56
0
2
Order By: Relevance
“…Atherosclerosis is a chronic inflammatory process that is characterized by deposition of fibrous tissues and fat in the intima of elastic arteries, resulting in thrombus formation and structural damage, characterized by thickening and hardening of the vessel walls, followed by loss of elasticity and narrowing of the lumen . There are four main pathological criteria for atherosclerosis: (i) the formation of “fatty streaks” that reduce the elasticity of arterial walls; (ii) fibrous plaques; (iii) atheromatous plaques; and (iv) thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis is a chronic inflammatory process that is characterized by deposition of fibrous tissues and fat in the intima of elastic arteries, resulting in thrombus formation and structural damage, characterized by thickening and hardening of the vessel walls, followed by loss of elasticity and narrowing of the lumen . There are four main pathological criteria for atherosclerosis: (i) the formation of “fatty streaks” that reduce the elasticity of arterial walls; (ii) fibrous plaques; (iii) atheromatous plaques; and (iv) thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…15 One of the most intriguing recent developments is the notion that local action of platelet microvesicles (commonly 100-200 nm in size) promotes vascular inflammation and lipid accumulation and is associated with development of subclinical lipid-rich atherosclerotic plaque. 16,17 Preclinical studies have confirmed vascular adhesion of platelets in early atherogenesis. In hyperlipidemic rabbits and in apolipoprotein-E-deficient mice receiving a high-fat diet, direct endothelial adhesion of ex vivo-labeled platelets at lesion-prone sites has been observed early in atherosclerosis, the extent of which increased with plaque progression.…”
Section: Platelet Activation and Adhesion In Atherogenesismentioning
confidence: 94%
“…Moreover, Huang et al [109] reported that increased circulating CD31+/annexin V+ EMPs and decreased circulating EPCs predict target organ damage in hypertensive patients. The higher concentrations of endothelial-derived MPs have been found in patients with acute coronary syndrome, sudden cardiac death due to acute coronary occlusion and stable angina [89]. Moreover, number of endothelial-derived MP (CD42-CD31+) closely and inversaly relate to indexes of microvascular obstruction in acute myocardial infarction patients [110].…”
Section: Endothelial Cells-derived Mpsmentioning
confidence: 99%
“…The leukocyte-derived MPs were found in higher concentrations in the patients with acute coronary syndrome and STEMI, asymptomatic atherosclerosis, obesity, diabetes, HF [89][90][91]. The monocyte CD14(+) MPs were implicated in the modulation of the post-acute coronary syndrome reparative response to injury [90].…”
Section: Leukocyte-derived Mpsmentioning
confidence: 99%